Design, synthesis, molecular docking and anticonvulsant evaluation of novel 6-iodo-2-phenyl-3-substituted-quinazolin-4(3H)-ones - Mohamed-Kamal Ibrahim; Khaled El-Adl; Ahmed A. Al-Karmalawy (Faculty of Pharmacy, Cairo University, 2015)
A new series of 6-iodo-2-phenyl-3-substituted-quinazolin-4(3H)-one (5-12a-b) derivatives were synthesized, evaluated for their anticonvulsant activity against pentylenetetrazole (PTZ)-induced seizures and maximal electroshock test and compared with the reference drugs phenobarbital sodium and methaqualone. The neurotoxicity was assessed using rotarod test. The molecular docking was performed for all the synthesized compounds to assess their binding affinities to GABA-A receptor in order to rationalize their anticonvulsant activities in a qualitative way. The data obtained from the molecular modeling were correlated with those obtained from the biological screening. Compounds 9a, 9b, 12a and 7a showed the highest anticonvulsant activities of this series with relatively low neurotoxicity and low toxicity in the median lethal dose test when compared with the reference drugs. The obtained results proved that the most active compounds could be a useful model for future design, adaptation and investigation to construct more active analogs.